Building ERP Solutions with Microsoft Dynamics NAV - Demiliani, Stefano; Demiliani, Stefano (Packt Publishing, 2017)
Create real-world enterprise solutions with NAV, Cloud, and the Microsoft stackAbout This BookIntegrate NAV with various offerings of the Microsoft stack to create enterprise-ready and service-oriented solutionsUse Power BI and Universal Windows Platform for effective data analysis and real-time tracking with NAVDiscover the services offered by Microsoft Azure and implement them in different industries using real-world case scenariosWho This Book Is ForThis book is for NAV developers and solution architects who need to implement real-world enterprise solutions based on Microsoft Dynamics NAV. Knowledge of the NAV programming language (C/AL) and C# language is recommended. Knowledge of ASP.NET and Visual Studio development would help, but is not necessary.What You Will LearnConfigure NAV Web Services and create external applications with Visual Studio, .NET, and .NET CoreSolve technical architectural problems by implementing enterprise solutions with NAVDevelop applications and solutions with Microsoft Dynamics NAV and the Microsoft technology stackCreate a Power BI dashboard for rich reporting and NAV data analysisFind out how to transmit your device location from a UWP application to NAV in order to implement a distributed solution for managing couriers in a sales companyMake the most of Microsoft Azure and its servicesCreate enterprise solutions with NAV by using Azure App ServiceUse Azure Service Bus for managing distributed NAV applicationsIn DetailImplementing Microsoft Dynamics NAV in the real world often requires you to integrate the ERP with external applications or solve complex architectural tasks in order to have a final successful project. This book will show you how to extend a Microsoft Dynamics NAV installation to the enterprise world in a practical way.The book starts with an introduction to Microsoft Dynamics NAV architecture and then moves on to advanced topics related to implementing real-world solutions based on NAV and external applications. You will learn how an enterprise distributed architecture with NAV at the core can be implemented.Through a series of real-world cases on every topic and every industry (sales, retail, manufacturing, distribution, healthcare, and so on), you'll see step by step how to efficiently solve a technical problem. These common problems encountered in a NAV implementation will be solved using the entire technology stack that Microsoft offers.By the end of the book, you will have the knowledge to efficiently solve certain scenarios, you will know which is the best solution architecture to propose to a customer and how to implement it.Style and approachTaking you through a variety of real-world use cases, the book will show you step by step all you need to know to tackle these problems and give you creative ideas to implement in related problems you might come across in the real world.